Anlotinib-associated pulmonary embolism in brainstem glioblastoma treatment: a case report - Zhao, Jia-Lan; Zhang, Yong-Li; Qu, Ke-Jun; Jiang, Yang-Yang; Li, Jiang-Lin; Zhou, Jia; Wu, Shu-Teng; Li, Jun-Wei (Frontiers in Oncology, 2025)
BackgroundGlioblastoma (GBM) is the most common and aggressive primary brain malignancy in adults. Diagnosis primarily relies on imaging techniques like CT scan and MRI, while pathological biopsy remains the diagnostic gold standard. Standard of care for newly diagnosed GBM includes maximal safe resection followed by radiotherapy and chemotherapy, although prognosis remains poor. GBM patients are at heightened risk for venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), with chemotherapy and targeted therapy further elevating this risk.Case summaryWe report a case of a patient with atypical cranial imaging findings, where initial assessments at both an external hospital and our institution were equivocal. A definitive GBM diagnosis was achieved only after biopsy. GBMs are highly vascularized malignant tumors. Anlotinib, an anti-angiogenic multi-kinase inhibitor, has been used to treat GBM. Following diagnosis, the patient received anlotinib therapy and subsequently developed PE, suspected as an anlotinib-induced adverse event.ConclusionAnlotinib may cause PE and should be used with caution. Clinicians should close coagulation monitoring following anlotinib treatment, including D-dimer testing and imaging (eg, CT), to ensure prompt diagnosis and timely treatment for PE. This case highlights the critical need for vigilant PE monitoring and prompt management in GBM patients on anlotinib therapy.